Facile synthesis of a novel photocatalyst with integrated features for industrial effluents treatment. Issue 3 (1st February 2022) - Bashir, Sheraz; Iqbal, Naseer; Jamil, Akmal; Alazmi, Amira; Shahid, Muhammad
Abstract: Faster charge transport, excellent charge separation, narrow bandgap energy, lower electron-hole pair recombination rate, and high visible light absorption are the key features of an ideal photocatalyst material. Undoubtedly, semiconductor-based photocatalysts having remarkable charge separation efficiency have attracted considerable attention for degrading hazardous organic pollutants from contaminated water. So herein, a novel composite of reduced graphene oxide (rGO) supported by gadolinium doped bismuth yttrium oxide (Gd-BiYO3 /rGO) was prepared by simple precipitation and ultrasonication method. The photocatalytic efficiency of the Gd-BiYO3 /rGO composite was examined comparatively with pure BiYO3 and Gd-BiYO3 samples to degrade Methylene Blue (MB) dye under visible light irradiation. The Gd doping and rGO incorporation into BiYO3 increased the conductivity, improved the charge transfer efficiency, and impeded the charge recombination, resulting in superior photocatalytic activity of Gd-BiYO3 /rGO. The kinetic studies exhibited the 96.2%, 61.5%, and 48.3% degradation of MB after 80 min irradiation of 1 SUN visible light under Gd-BiYO3 /rGO, Gd-BiYO3, and BiYO3, respectively. The Gd-BiYO3 /rGO composite degraded the MB dye at a rate (k = 0.0328 min -1 ) that is 5.05 and 2.68-fold higher than pure BiYO3 and Gd-BiYO3, correspondingly. The transient photocurrent response of Gd-BiYO3 /rGO was comparatively 4.7 and 2.8 times greater than that of BiYO3 and Gd-BiYO3 photocatalysts, respectively. The dominant photocatalytic performance of Gd-BiYO3 /rGO is primarily ascribed to the formation of heterojunctions between rGO nanosheets and Gd-BiYO3, which facilitate higher visible light absorbance, effective charge separation, and transfer through interfacial layers, more dye adsorption, lower charge transfer resistance, and hamper electron-hole pair recombination. Overall, the electrochemical results suggest that the current study provides an effective way to synthesize a heterostructure photocatalyst for removing organic pollutants from industrial effluents. Graphical abstract: Image 1